Training and Development Strategy and Its Role in Organizational Performance in FMCG Organizations - Al-Nowaiser, Mashael (The journal of contemporary issues in business and government, 2022)
There is a lot of demand on FMCG companies to transform into "Learning Organizations" in order to survive in the current global economic climate and remain competitive. Multiple research methods were used to compile these results. Examining the connection between training and development initiatives and organisational effectiveness is the major focus of this study. and to isolate the impact of training and development (TND) initiatives and "Line Managers" in fast-moving consumer goods (FMCG) businesses. “Training and development strategy alignment, Training Needs Analysis, and line managers” have active engagement in formalisation and training including employment and assessment, are all independent elements. As a dependent variable, organisational performance is examined here as an outcome of a well- executed training and development strategy. The current study uses a Questionnaire as an instrument. A convenience sampling method and sample size are 100 (employees) from various divisions of a global FMCG firm have been chosen. Hypothesis has been tested with correlation techniques. Findings show that “training and development” plays very vital role in the development and performance of organizations. And the role of Line managers also shows positive result with training and development.